Effects of surface treatment on the critical energy release rates of welded joints between glass fiber reinforced polypropylene and a metal. (June 2016) - Shimamoto, K.; Sekiguchi, Y.; Sato, C.
Abstract: Fiber reinforced plastics (FRPs) are in high demand as a means to reduce the weight of vehicle structures. When utilizing FRPs with other materials, the joining technology between them is a key technical issue because the joining methods are related to the safety of the vehicle and also restrict the vehicle design. Polypropylene (PP) is a widely utilized thermoplastic material in the automotive industry because of its reasonable price and high resistance to water absorption. Therefore, PP has a potential to be applied to a matrix resin for FRPs. When PP is utilized as a matrix resin for FRPs, welding is a joining method that has a low cost and high productivity between fiber reinforced polypropylene (FRPP) and metals. However, the welding strength between a FRPP and a metal does not have sufficient strength to be used in the structures. Therefore, in this paper, a chemical etching treatment and sandblasting treatment were applied to the surfaces of metal adherends that were used to increase the welding strength to verify the effect of mechanical interlocking, and the critical energy release rates of the welded joints were measured on welded double cantilever beam (DCB) specimens. The experimental results indicate that the chemical etching treatment is a very effective surface treatment method, with the resulting metal surface exhibiting a drastic increase of welding strength because the treatment made the surface morphology complex enough to enhance the effect of mechanical interlocking and obtain a higher bonding strength compared to the morphology produced via sandblasting. In addition, the employed chemical etching methods increase the bonding strength between GFRPP and metal to a level that exceeds the interlaminar strength of GFRPP. Therefore, the chemical etching depth did not affect the welding strength, and the maximum bonding strength only depends on the interlaminar strength of the GFRPP.